Studi Bioekivalensi Obat Paracetamol Generik Dan Non Generik Secara In Vitro - Siti Mutaharah; Saftia Aryzki; Rina Saputri; Yusuf Anggoro Mukti (CV. Wadah Publikasi Cendekia, 2023)
Drugs are one component of health that is irreplaceable in order to improve public health status. There are 2 types of drugs circulating in the market, namely generic and non-generic. Paracetamol is classified as a class 1 biopharamcetic drug which is formulated as a product with high solubility in water and has high intestinal permeability, almost 100% absorption can be expected at least as much as 85% of the soluble product in in vitro testing. In vitro testing was carried out for 180 minutes with a span of 15 minutes using generic paracetamol and patented paracetamol to determine whether there is a difference in the quality of the drugs and to make comparisons with the aim of knowing their bioequivalence.